“Técnicas activas para el desarrollo de la Motricidad en los niños y niñas en Educación Inicial de la unidad educativa Cinco de Junio del Cantón Riobamba, Provincia de Chimborazo durante el periodo 2011. 2012” - Lara Jara, Mónica del Pilar (2017)
The present research work arose from the diagnosis carried out in the institutional planning, after analyzing the problems the eminently pedagogical topic was prioritized, hence the study of the project was born. The exploration was done on the facts themselves and their reality, which made it possible to configure the present work. The information reflected the educational reality of its constituent elements, so it is of vital importance to consider its experience in the development of the cognitive abilities of children. The methodology used and implemented for the collection of the information was carried out through the technique of observation in which the active skills for the development of fine and coarse motor are comprised. The study sample was composed of 42 children, who were subjects of analysis and interpretation based on the fundamentals of pedagogy applied to the development of skills that demonstrate cognitive growth in the first years of teaching corresponding to the initial levels. For the accomplishment of this work, some methods were considered: the synthetic and inductive deductive analytical, those that allowed to follow a process in the deductive field; As well as the compilation, organization and systematization of the different data. Finally, the study raised contributed to the children of the educational unit "Cinco de Junio", making possible that the active techniques contribute to the development of their motor skills. It will also serve as a basis for raising new' research topics in what the progress of recruitment in early childhood means.